New perspectives on Microsoft Access 2000 : introductory. - Adamski, Joseph J.; Hommel, Charles; Finnegan, Kathleen T. (Cambridge, MA : Course Technology, 1999)
This book is divided into seven parts: Introduction to Microsoft Access 2000; Maintaining a Database; Querying a Database; Creating Forms and Reports; Creating More Advanced Queries and Custom Forms; Customizing Reports and Integrating Access with Other Programs; Working with HTML Documents, Data Access Pages, and Hyperlink Fields; and Relational Databases and Database Design.
Keywords: Computer; Microsoft Access; Microsoft Access (Computer file)